แนวทางการพัฒนาผลิตภัณฑ์จากไม้ไผ่ ให้เป็นผลิตภัณฑ์ระดับ 5 ดาว ของกลุ่มพัฒนาอาชีพผลิตภัณฑ์จากไม้ไผ่ บ้านแคนคำ ตำบลไร่น้อย อำเภอเมืองอุบลราชธานี จังหวัดอุบลราชธานี - พรวานิชพงศ์, อัมพร; ฤทธิรอด, ธีระ (JOURNAL OF LANGUAGE, RELIGION AND CULTURE, 2016)
การศึกษานี้มีวัตถุประสงค์เพื่อ 1) ศึกษาสภาพการพัฒนาผลิตภัณฑ์จากไม้ไผ่ ปัญหาและอุปสรรคของการพัฒนาผลิตภัณฑ์จากไม้ไผ่ ให้เป็นผลิตภัณฑ์ระดับ 5 ดาว 2) หาแนวทางการพัฒนาผลิตภัณฑ์จากไม้ไผ่ ให้เป็นผลิตภัณฑ์ระดับ 5 ดาว งานวิจัยนี้เป็นการวิจัยเชิงคุณภาพ (Qualitative Research) โดยเก็บข้อมูลภาคสนาม การสัมภาษณ์เจาะลึกเป็นรายบุคคลจากกลุ่มเป้าหมายจำนวน 10 คน ผู้รับผลิตภัณฑ์ไปจำหน่ายและผู้ซื้อผลิตภัณฑ์ จำนวน 5 คน และพัฒนากรประจำตำบล จำนวน 1 คน ผลการศึกษานี้พบว่า 1) ปัญหาและอุปสรรคของกลุ่มพัฒนาอาชีพผลิตภัณฑ์จากไม้ไผ่ ให้เป็นผลิตภัณฑ์ระดับ 5 ดาว มีดังนี้ 1.1) การผลิตได้ น้อยกว่าร้อยละ 30 ของปีที่ผ่านมาและการผลิตมีผลกระทบต่อสิ่งแวดล้อม 1.2) รูปแบบพัฒนาผลิตภัณฑ์ไม่แตกต่างจากกลุ่มอื่นและผลิตภัณฑ์สื่อถึงภูมิปัญญาไทยน้อย 1.3) การออกแบบบรรจุภัณฑ์ไม่มีเอกลักษณ์ของท้องถิ่นและไม่มีการนำเสนอเรื่องราวตำนานของผลิตภัณฑ์ 1.4) กลุ่มมีส่วนร่วมกับชุมชนน้อย 1.5) รายได้ในการจัดจำหน่ายสินค้าเทียบกับปีที่ผ่านมาเพิ่มขึ้นไม่เกินร้อยละ 25 การขยายตลาดน้อยและสินค้ายังไม่สามารถจำหน่ายยังห้างใหญ่ๆ หรือขายในต่างประเทศได้ 1.6) กลุ่มไม่มีการจัดทำบัญชีอย่างเป็นระบบและผลการศึกษาสะท้อนจุดแข็งของกลุ่ม 3 ประเด็น ได้แก่ สินค้ามีราคาถูกเมื่อเทียบกับคู่แข่ง สินค้ามีลักษณะเด่น ดึงดูดความสนใจ และมีความรู้ความชำนาญทางเทคนิค และจุดอ่อนของกลุ่ม 3 ประเด็น ได้แก่ มีเทคโนโลยีล้าสมัย มีเงินทุนหมุนเวียนไม่เพียงพอ และสินค้าไม่พอขายในช่วงเทศกาล ดังนั้น เพื่อให้กลุ่มอาชีพผลิตภัณฑ์จากไม้ไผ่ บ้านแคนคำ ตำบลไร่น้อย อำเภอเมืองอุบลราชธานี จังหวัดอุบลราชธานี ได้เป็นผลิตภัณฑ์ระดับ 5 ดาว จึงควรมีการพัฒนาใน 3 ประเด็น ดังนี้ 1) การอบรมการออกแบบผลิตภัณฑ์ 2) การประชาสัมพันธ์ผลิตภัณฑ์กลุ่มพัฒนาอาชีพผลิตภัณฑ์จากไม้ไผ่ 3) การอบรมการจัดทำบัญชีให้แก่กลุ่มอาชีพ โดยทำเป็นโครงการซึ่งองค์การบริหารส่วนตำบลไร่น้อยเป็นผู้สนับสนุนงบประมาณ Guideline for Bamboo Product Development to Become 5 Stars Product of Career Development Group from Bamboo Product Ban Khan Kham Rai Noi Sub-District, Muang Ubon Ratchathani District, Ubon Ratchathani Province The objective of this research were 1) to study the state of bamboo product development, problems and limitations of career development group from bamboo product to become five stars product 2) to find the approach of Bamboo product development to become the five stars product. This study was the qualitative research and the data was gathered in field survey by In-depth interview method from 10 ordinary people of related target group, 5 distributors and 1 Sub-District developer. From the research, it revealed that 1) the state of bamboo product development, problems and limitations of career development group from bamboo product were found as following 1.1) The production was less than 30 % when compared with the prior year and it also affected on the environment. 1.2) the model of product was quite not different from other competitors and the product displayed the Thai local wisdom insufficiently.1.3) the package design could not express the unique of local and there was not the description of the product history. 1.4) Career development group had less opportunity to participate the community activity. 1.5) When compared the revenue of product distribution with the prior year, it was found that it increased in maximum 25%, it also found that the increasing of marketing segmentation was less and most products could not displayed in the Supermarket in the grand department stores and it also could not export to aboard. 1.6) Career group was lack of accounting system systemically. The strength of product were found that when compared with other competitors, the price of product was quite cheap, the product was outstanding and attractive attributes, the producer was more skill and technique, the weakness of product were found that the technology for production was out of date, lack of working capital, and lack of product during high season, therefore in order to become the five stars product, it should be developed as the following 1) the training course of product packaging design 2) the public relation of bamboo product from the career development group from bamboo product 3) the training course of accounting system as project and the budget was supported by Rai Noi Sub-District Administration Organization.